Subtle neuropsychiatric and neurocognitive changes in hereditary gelsolin amyloidosis (AGel amyloidosis) - Mari Kantanen (PeerJ, 2014)
Hereditary gelsolin amyloidosis (AGel amyloidosis) is an autosomal dominant form of systemic amyloidosis caused by a c.640G>A or c.640G>T mutation in the gene coding for gelsolin. Principal clinical manifestations include corneal lattice dystrophy, cranial neuropathy and cutis laxa with vascular fragility. Signs of minor CNS involvement have also been observed, possibly related to cerebral amyloid angiopathy (CAA). To investigate further if AGel amyloidosis carries a risk for a specific neuropsychological or psychiatric symptomatology we studied 35 AGel patients and 29 control subjects. Neuropsychological tests showed abnormalities in visuocontructional and -spatial performance in AGel patients, also some indication of problems in processing efficacy was found. At psychiatric evaluation the patient group showed more psychiatric symptomatology, mainly depression. In brain MRI, available in 16 patients and 14 controls, we found microhemorrhages or microcalcifications only in the patient group, although the number of findings was small. Our study shows that AGel amyloidosis can be associated with visuoconstructional problems and depression, but severe neuropsychiatric involvement is not characteristic. The gelsolin mutation may even induce cerebrovascular fragility, but further epidemiological and histopathological as well as longitudinal follow-up studies are needed to clarify gelsolin-related vascular pathology and its clinical consequences.